소규모하수처리시설의 이차침전조 내통길이 변화를 통한 탈수여액의 처리 - 최정수(Jung Su Choi); 김현구(Hyun Gu Kim); 이동호(Dong Ho Lee); 주현종(Hyun Jong Joo) (Daehan hwan'gyeong gonghag hoeji, 2013)
The purpose of this study is to evaluate a de-watering filtrate treatment and the possibility of securing biological treatment capacity by changing the structure of the secondary clarifier. Accordingly, the column test was conducted to determine the effect of polymer in the de-watering filtrate on sludge sedimentation. Also, the characteristics of de-watering filtrate processing was evaluated through batch test and continuous processing operation. The results showed that sludge settling velocity increased with higher polymer concentration, and that effluent SS concentration was found to decrease. Regarding processing characteristics of de-watering filtrate, the removal efficiency of TSS and TBOD5 increased as the length of secondary clarifier was longer. Also, comparing injections into anoxic tank and secondary clarifier, de-watering filtrate by continuous infusion treatment process showed stability in both conditions. Therefore, by modifying the structure of secondary clarifier, efficient processing of de-watering filtrate is expected to be possible and processing capacity of small sewage treatment plants is considered to be improved. 본 연구의 목적은 이차침전조의 구조개선을 통해 탈수여액 처리와 생물학적 처리용량 확보의 가능성을 평가하는데 있다. 이에 따른 연구의 절차로는 탈수여액 내 함유된 polymer가 슬러지 침전에 미치는 영향을 column test를 통해 평가하였으며, 회분식 실험과 연속식 처리공정운전을 통해 탈수여액의 처리 특성을 평가하였다. 그 결과 슬러지 침강속도는 polymer 주입율이 증가할 수 록 증가하는 경향을 나타냈으며, 상징수의 SS 농도는 감소하는 것을 알 수 있었다. 탈수여액의 처리 특성은 이차침전조 내통 길이가 길수록 탈수여액 내 함유된 TSS 및 TBOD5의 제거효율이 증가하는 경향을 보였다. 또한 연속식 처리공정 적용 결과는 탈수여액 주입위치를 각각 무산소조와 이차침전조에 주입한 경우를 비교하였을 때 두 조건에서 모두 안정적인 방류수질을 보였다. 따라서 이차침전조의 구조개선을 통해 탈수여액의 효율적인 처리가 가능 할 것으로 판단되며, 소규모 하수처리장의 경우 처리용량 부족 문제를 해결할 수 있을 것으로 사료된다.